From Inhibition of GABA-A Receptor-Mediated Synaptic Transmission by Conventional Antidepressants to Negative Allosteric Modulators of Alpha5- GABA-A Receptors as Putative Fast-Acting Antidepressant Drugs: Closing the Circle? - Fernández-Teruel, Alberto (Current Neuropharmacology, 2022)
The present perspective paper shortly and specifically addresses the issues of whether inhibition of GABA-A receptor-mediated synaptic transmission may be involved in antidepressantlike actions and the therapeutic effects of conventional antidepressant (AD) drugs, and whether the recent development of negative allosteric modulators (NAMs) of the alpha5-GABA-A receptor may constitute significant progress in our knowledge on the neurobiology and the treatment of depression.
Keywords: conventional antidepressants